ANALISIS KUALITAS PELAYANAN FRONTLINER PADA NASABAH PT BANK BNI SYARIAH KC PANORAMA BENGKULU - Tri Rahayu; Yanto Yanto; Indria Indria (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
This study aims to find out how the frontliner services for customers of PT Bank BNI Syariah KC Panorama Bengkulu. This research is a descriptive study with a qualitative approach. Descriptive qualitative research aims to explain the phenomena as deeply as possible that occur in the field and present data systematically, factually, and accurately regarding the facts or phenomena that occur in the field. Data collection is done by means of initial observation, interviews and documentation. Data analysis in this study uses three components, namely data reduction, data presentation and conclusion. The results showed that the quality of service of PTBank BNI Syariah KC Panorama Bengkulu has implemented five dimensions of service quality according to Parasuarman et al, namely Tangible, Reliability,Responsivity, Assurance and Emphaty, but there are some things that have not gone according to customer wishes such as the inability of waiting room at PT Bank BNI Syariah KC Panorama Bengkulu, where the waiting room is too small, sometimes busy customers have to wait outside, then the lack of seats waiting sometimes customers waiting to stand up remember the condition of small and narrow room and for EDC tools that have to swipe cards repeatedly because the EDC engine is error.